European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) Position Statement on Dermatologic Ultrasound - Alfageme, Fernando; Wortsman, Ximena; Catalano, Orlando; Roustan, Gaston; Crisan, Maria; Crisan, Diana; Gaitini, Diana E.; Cerezo, Eugenio; Badea, Radu (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Dermatologic ultrasound is a recent application of ultrasound for the evaluation of healthy skin and appendages and their diseases. Although the scientific literature regarding this application is still not sufficient for evidence-based guidelines, general recommendations issued by scientific societies are necessary. The EFSUMB (European Federation of Societies for Ultrasound in Medicine and Biology) steering committee for dermatologic ultrasound has developed a series of consensus position statements regarding the main fields of dermatologic ultrasound (technical requirement, normal skin and appendages, inflammatory skin diseases, tumoral skin diseases, aesthetic dermatology and practice-training requirements). This document is the foundation for future evidence-based recommendations and guidelines for dermatologic ultrasound practice.
Keywords: dermatologic ultrasound; guidelines and recommendations; skin ultrasound